Social Class Identity, Public Service Satisfaction, and Happiness of Residents: The Mediating Role of Social Trust - Zhou, Xiaogang; Chen, Shuilin; Chen, Lu; Li, Liqing (Frontiers in Psychology, 2021)
Happiness is the eternal pursuit of mankind, and it is also the ultimate goal of social governance and national development. Based on the data of Chinese General Social Survey (CGSS), this paper uses Structural Equation Model to analyze the influence of social class identity and public service satisfaction on the happiness of residents among different groups. The effect of public service satisfaction and social trust between social class identity and the happiness of residents was tested by Deviation Corrected Bootstrap Method. The empirical results show that social class identity, social trust, and public service satisfaction all have a significant positive impact on residents’ happiness. The influence coefficients of social class identity on the happiness of residents and on the satisfaction degree of public service in the post-70s group was greater than that of the post-80s group and the post-90s group. The influence coefficients of social class identity on happiness and public service satisfaction of non-agricultural household residents is greater than that of agricultural household residents. Therefore, in order to improve the happiness of the residents, we should make new breakthroughs in the equality of quality and quality of public services, promote the integration of urban and rural areas, highlight the key areas of rural development, and increase the construction of public basic services of agricultural household residents.